A review on the potential of tissue culture technique in producing an elite oil palm clone as compared to conventional propagation / Adhwa Hakim Che Wan - Che Wan, Adhwa Hakim (Faculty of Plantation and Agrotechnology, 2016)
Propagation of oil palm will enhance the production of planting materials to fulfill the demand. This can be done through modem propagation or conventional propagation. The modem propagation through plant tissue culture will use explant that will undergo several processes with controlled or aseptic condition, while conventional propagation will use seed. However, each types of propagation have their own advantages and disadvantages. But, the main objectives of both types propagation remain the same. This review was done to identify deeply about the potential of types propagation in producing an elite oil palm (seedling or plant Jets) and other special characteristics within given period. Through narrative reviews methodology, the tissue culture technique has highly potential in producing large quantity of elite oil palm planting materials as compared with conventional propagation. Due to non-limited source of material to undergo propagation, high rate of planting material production per source material, several techniques were used to produce high rate of planting material productions under controllable condition, the potential yield and uniformity growth is high, the economic lifespan lead to much longer and also operation cost tend to reduce in future. The tissue culture propagation embraced by producer to be implemented as their technique in produce large scale of planting materials of oil palm.